Health promotion to mothers of preterm infants: nursing action in hospital discharge - Duarte, Anailza de Souza; Santos, Willys da Silva; Silva, Leide Dayane Barbosa da; Oliveira, Joseph Dimas de; Sampaio, Karla Jimena Araújo de Jesus (Rev Rene, 2010)
Prematurity is the main cause for hospitalization in neonatal units being considered a problem of Public Health. It was aimed to know the view of the nursing team on the accomplishment of actions with mothers facing hospital discharge of preterm infants. This is a qualitative study carried out at a hospital in Barbalha-CE-Brazil, with twelve members of the nursing team that act with mothers of preterm infants in neonatal unit, in 2008. The data collected were analyzed through speeches categorization and method of content analysis. The following thematic categories were identifi ed in the study: maternal preparation for the preterm infant discharge; nursing orientations for preterm infant care; and diffi culties in maternal preparation for the preterm infant discharge. It was verifi ed that the accomplishment of Health Education in preterm infants’ discharge is important to develop maternal trust in the care to the child, infl uencing in the post-discharge quality of life.